2013
DOI: 10.1111/ctr.12119
|View full text |Cite
|
Sign up to set email alerts
|

Completely steroid‐free immunosuppression in liver transplantation: a randomized study

Abstract: Introduction Corticosteroids (CS) have been standard immunosuppression to prevent and treat rejection. However, CS are associated with increased risk of infection, obesity, hypertension, hyperlipidemia, diabetes, and accelerated hepatitis C virus (HCV) recurrence post‐orthotopic liver transplantation (OLT). This study assesses the safety and efficacy of CS‐free immunosuppressive regimen in adult OLT. Methods A two‐yr, prospective, randomized study of CS with delayed withdrawal (CS) or CS‐free regimen with basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Moreover, previous studies using basiliximab induction or evaluating mycophenolate in LT allowed either to delay the introduction or decrease the exposure to tacrolimus to prevent toxicity (3,4). However, in the current RCT (1), the mean trough concentrations of tacrolimus within the first month were as high as 11.3 ng/mL in the four immunosuppressant arm (1). In a recent meta-analysis of 32 RCT, tacrolimus trough concentrations 6-10 ng/mL had similar antirejection effects and halved renal impairment rates (5).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, previous studies using basiliximab induction or evaluating mycophenolate in LT allowed either to delay the introduction or decrease the exposure to tacrolimus to prevent toxicity (3,4). However, in the current RCT (1), the mean trough concentrations of tacrolimus within the first month were as high as 11.3 ng/mL in the four immunosuppressant arm (1). In a recent meta-analysis of 32 RCT, tacrolimus trough concentrations 6-10 ng/mL had similar antirejection effects and halved renal impairment rates (5).…”
mentioning
confidence: 63%
“…To the editor The randomized controlled trial (RCT) by Ramirez et al (1) compared two immunosuppression regimens after liver transplantation (LT): basiliximab induction, full-dose tacrolimus, and mycophenolate with or without steroids. However, after LT, acute cellular rejection is no longer a major cause of graft loss, while renal impairment, infections, cardiovascular events, and malignancy form a rising burden.…”
mentioning
confidence: 99%
“…There are still recent randomized trials using quadruple immunosuppression as a standard of care for liver transplantation patients [69], leading to unnecessarily reduced rejection rates, a more severe recurrence of hepatitis C, more frequent infections and new-onset diabetes [70]. A certain grade of acute rejection early after liver transplantation provides a benefit in terms of long-term survival [34,71], and it has been hypothesized that a complete suppression of acute rejection may prevent operational tolerance, and therefore it is neither necessary nor appropriate [71,72].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In a trial of 39 patients randomized to a corticosteroid-containing (n = 20) versus corticosteroid-free regimen (n = 19), rates of obesity after 2 years were not significantly different. 42 In a European review of 296 recipients, the type of immunosuppressive drug had no effect on waist circumference or BMI post-LT. 43 A recent retrospective review of 455 recipients similarly showed no significant association between immunosuppression type and prevalence of obesity at 1 year after LT: tacrolimus versus other (odds ratio [OR], 1.18; P = 0.702), cyclosporine (CSA) versus other (OR, 0.78; P = 0.651), and tacrolimus versus CSA (OR, 1.58; P = 0.347). 44 Although sirolimus-based immunosuppression was associated with less weight gain posttransplant in a large renal transplant population, no data are available in LT. 45 At this time, we do not suggest making any changes to the standard immunosuppression regimen based on recipient BMI.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%